High-spatial resolution long-mid-infrared observations of massive star-forming regions: Local star formation sequence. (2nd November 2021) - Uchiyama, Mizuho; Miyata, Takashi; Sako, Shigeyuki; Kamizuka, Takafumi; Asano, Kentaro; Nakamura, Tomohiko; Yamashita, Takuya; Fujiyoshi, Takuya; Yoneda, Mizuki; Konishi, Masahiro; Koshida, Shintaro; Motohara, Kentaro; et al.
Abstract: The formation of massive stars in dense and cold molecular clouds is a fundamental problem in star formation. In this work, we studied three compact massive star-forming regions, M8E, RAFGL 6366S, and IRAS 18317−0513, to investigate the environment of massive star formation, specifically the possibility of a local feedback process. Our new mid-infrared observations using miniTAO/MAX38 at 31 and 37 μm resolved individual objects in each region and allowed us to obtain their individual luminosities and masses. Together with existence/absence of ultra-compact H ii regions, it is suggested that less-massive objects are more evolved than the more-massive objects in two out of the three regions. Because the objects that are more massive evolve faster, those that are less massive form earlier. This formation trend of local mass-sequential star was first suggested in 0.1 pc-scale massive star-forming regions. Therefore, feedback, such as outflows, jets, or radiative heating, from previously formed lower-mass young stellar objects might affect the environment of parental clouds and lead to next-generation massive young stellar objects.